Magnetization Transfer Measurements of the Hippocampus in Patients with Alzheimer's Disease, Vascular Dementia, and Other Types of Dementia - Hanyu, Haruo; Asano, Tetsuichi; Iwamoto, Toshihiko; Takasaki, Masaru; Shindo, Hiroaki; Abe, Kimihiko (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Although atrophy of structures in the medial temporal lobe has been considered an indication of Alzheimer's disease (AD), atrophic changes on MR images have also been associated with other dementing diseases and are not specific to AD. This study was undertaken to determine whether characteristic alterations in the hippocampus of patients with AD are detectable with magnetization transfer (MT) imaging.METHODS: Coronal MT imaging was performed in 35 patients with probable AD, in 14 patients with vascular dementia, in 13 patients with other types of dementia, and in 23 control subjects to measure MT ratios of the hippocampus. Medial temporal lobe atrophy was graded subjectively on a five-point scale.RESULTS: Scores of medial temporal lobe atrophy in all dementia groups were significantly higher than those in control subjects, but no differences were found among the dementia groups. MT ratios in the hippocampus were significantly lower in patients with AD than in those with non-AD dementia and in the control subjects; however, no differences were found between the non-AD dementia patients and the control subjects. MT ratio measurements were better than visual analysis of atrophy for differentiating AD patients from those with non-AD dementia (an overall discrimination rate of 77% versus 65%). MT ratios significantly correlated with scores on the Mini-Mental State Examination and with medial temporal lobe atrophy in AD patients but not in patients with non-AD dementia.CONCLUSION: MT measurements may be more specific than visual analysis in detecting structural damage of the hippocampus in AD patients and might be useful in discriminating AD from vascular dementia and other types of dementia.